2011
DOI: 10.2165/11593330-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy for Children in Resource-Limited Settings

Abstract: WHO antiretroviral treatment guidelines for HIV-infected children have influenced the design of treatment programmes in resource-limited settings. This review analyses the latest WHO first- and second-line regimen recommendations. The recommendation to use lopinavir/ritonavir-containing first-line regimens in young children with prior non-nucleoside reverse transcriptase inhibitor (NNRTI) exposure is based on good quality evidence. Recent research suggests that lopinavir/ritonavir-containing first-line regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…[104] The best choice could be a salvage potent PI with high genetic barrier to resistance, such as DRV/r. [82,104,105] Recent data has shown that integrase inhibitors such as raltegravir and elvitegravir are also valuable in pediatric treatment. [104106] Finally, successful 3rd-line therapy of pediatric patients is hindered by the lack of pediatric formulations and high costs, with dosing especially problematic for children younger than 6 years, largely a result of the low priority that is given globally to the development of pediatric formulations and regimens.…”
Section: Discussionmentioning
confidence: 99%
“…[104] The best choice could be a salvage potent PI with high genetic barrier to resistance, such as DRV/r. [82,104,105] Recent data has shown that integrase inhibitors such as raltegravir and elvitegravir are also valuable in pediatric treatment. [104106] Finally, successful 3rd-line therapy of pediatric patients is hindered by the lack of pediatric formulations and high costs, with dosing especially problematic for children younger than 6 years, largely a result of the low priority that is given globally to the development of pediatric formulations and regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This increased access to first-line ART in children means that, over time, more children will fail first-line regimens and require second-line ART, particularly in poorly monitored or rural clinics [17], [18]. Unfortunately, in many resource-limited settings, access to second-line pediatric ART is challenging and options are very limited [19].…”
Section: Discussionmentioning
confidence: 99%
“…Given the intermediate level of transmitted NNRTI resistance and evidence of inferior viral suppression when used as first or second-line ART, this currently leaves limited options for children in South Africa after they fail PI-based first- or second-line therapy. Although Darunavir and Tipranavir have shown promising efficacy with limited toxicity in treatment-experienced children with significant PI resistance mutations, unfortunately these agents are not widely accessible to children in South Africa or other resource-limited settings at this time [19], [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…This finding in children without NVP exposure has major implications since LPV/r is more expensive, the liquid formulation requires refrigeration, and it is less palatable than NVP. 8 Our objectives were to investigate whether the differences between NVP- and LPV/r-based ART observed in children with PrNVP differed significantly from those with no PrNVP, identify other predictors of virologic and clinical response, and determine whether treatment differences depended on these other predictors.…”
mentioning
confidence: 99%